One‐step anchored polymers via phenolamine bionic design on textile‐based heater for application in personal heat management. Issue 17 (15th December 2021) - Du, Peibo; Guo, Zhiguang; Li, Yonghe; Zhang, Jinping; Muhammad, Javed; Cai, Zaisheng; Ge, Fengyan
Abstract: Flexible electronic fabrics urgently need to solve the problem of adhesion between the conductive layer and the fabric substrates. Inspired by phenamine bionics, we designed and fabricated copper nanoparticle conductive network/nylon 6 woven fabric (CNNs/NWF) wearable heaters through rapid co‐deposited of tannic acid and polyethyleneimine (PEI) by using CuSO4 /H2 O2 as a trigger. The grafted TA/PEI interface is capable of anchoring on the fabric surface via covalent and non‐covalent bonds on the one hand and providing an ideal platform to absorb and reduce catalyst Ag + to facilitate subsequent electroless deposition on the other. Furthermore, the electrical heater could rise temperature from 14.6 to 152.6°C within 90 s under 1.5 V voltage, better than that of recently reported literature. The heater had a splendid conductivity (sheet resistance R0 ≈ 0.0086 Ω sq −1 ) and remain stable after 1000 bending cycle tests (normalized resistance R/R0 ≈ 2.5). Furthermore, the heater could meet 50 standard washing tests, satisfying the essential needs of the wearable devices. The deviation between the simulated data and the measured data was no more than 10% by the simulation of the finite elemental analysis. This study might provide a viable source for wearable heating devices. Abstract :